Outcomes of rescue therapy in acute severe ulcerative colitis: data from the United Kingdom inflammatory bowel disease audit. Issue 8 (4th September 2013) - Lynch, R. W.; Lowe, D.; Protheroe, A.; Driscoll, R.; Rhodes, J. M.; Arnott, I. D. R.
Summary: Background: Approximately one third of patients with acute severe ulcerative colitis (ASUC) fail response to steroids. Ciclosporin and anti‐TNFα are proven second‐line therapies, but evidence of their efficacy has come mainly from tertiary centres and/or selective clinical trial recruitment. Aim: To assess ASUC outcomes in a large unselected cohort. Methods: UK‐wide audits of IBD care were conducted in 2008 (209 hospital sites) and 2010 (198 hospital sites), covering >87% of admitting hospitals. Each site entered data from 20 consecutive UC admissions onto a web‐based proforma. Admissions included 852 (2008) and 984 (2010) with ASUC, accounting for 35% and 39% of UC admissions, respectively. Results: ASUC in‐hospital mortality was 1.2% in 2008; 0.7% in 2010 ( P = 0.22). Response to first‐line steroid therapy was 61% (2008); 58% (2010) and mortality was higher in non‐responders: 2008: 2.9% (9/315) vs. 0.19% (1/537; P < 0.001); 2010: 1.8% (7/391) vs. 0.0% (0/593; P = 0.002). In 2010, more patients (56%) received second‐line medical therapy than in 2008 (47%, P = 0.02). In‐hospital mortality was similar to second‐line medical therapy vs. surgery without further medical therapy; 2008: 2.7% vs. 2.8%, P = 0.99; 2010: 0.9% vs. 3.1%, P = 0.17. Second‐line therapy response was more frequently observed with anti‐TNFα than ciclosporin: (2008: 76% vs. 46%, P < 0.001; 2010: 80% vs. 58%, P < 0.001). Conclusions: Mortality in acute severe ulcerative colitis was low, but higher in steroid non‐responders. Patients treated with second‐line medical therapies had no higher risk of in‐hospital mortality than those undergoing surgery. Second‐line 'rescue' medical therapy usage is increasing; however, ciclosporin response rates were relatively low.